THE DEVELOPMENT OF FINANCIAL MANAGEMENT MODEL FOR SCHOOL-BASED 9-YEAR BASIC EDUCATION LEARNING OBLIGATION IN KABUPATEN KUDUS - Rifiani, Yuli; Widodo, Joko; Kardoyo, Kardoyo; Haryono, Haryono (The Journal of Educational Development, 2016)
This study aimed to develop a financial management model for school-based 9-year basic education learning obligatory in the District of Kudus, Central Java. This study employed a Research and Development approach, in which the actual model obtained from the preliminary study was developed into a model design which was appropriate with the ideal condition in the District. Then, the final model of financial management for school-based 9-year basic education was determined through a focused group discussion attended by practitioners as well as experts in the related field. The results of the data analysis show that the financial model of basic education which had been implemented so far was not appropriate any longer given that the financial aid provided by the central government along with the provincial as well as district government on the basis of the number of students without taking into account the differential factors was not in line with the real needs of the schools. Therefore, it is necessary to develop a financial model of the basic education by considering achievement as the standard measure, in which the School Operational Aid (BOS) from the central and provincial government remains based on the number of students annually, while the subsidy from the residential government is still capable of covering the lack of the whole school needs under the conditions that the school is obliged to (1) arrange the School Budget and Activity Plan (RKAS) on the basis of EDS, (2) arrange the prioritized programs on the basis of the school vision and mission by (3) considering the school status, 4) average scores of the National Examinations (UN) and other achievements. The theoretical implication is that the model resulted from this study confirms Grubb, Rebbeca Allen’s theory that the students’ achievement is determined by fund; it also confirms Psacaropoulos that quality education requires high investment and that this development model is the realization of financial management functions as they were proposed by Harold Thomas Jones, and Warsono as well as the financial management theory proposed by Blocher.